Delineation of the innate and adaptive T-cell immune outcome in the human host in response to Campylobacter jejuni infection. - Lindsey A Edwards (Public Library of Science (PLoS), 2010)
Background Campylobacter jejuni is the most prevalent cause of bacterial gastroenteritis worldwide. Despite the significant health burden this infection presents, molecular understanding of C. jejuni-mediated disease pathogenesis remains poorly defined. Here, we report the characterisation of the early, innate immune response to C. jejuni using an ex-vivo human gut model of infection. Secondly, impact of bacterial-driven dendritic cell activation on T-cell mediated immunity was also sought. Methodology Healthy, control paediatric terminal ileum or colonic biopsy tissue was infected with C. jejuni for 8-12 hours. Bacterial colonisation was followed by confocal microscopy and mucosal innate immune responses measured by ELISA. Marked induction of IFNγ with modest increase in IL-22 and IL-17A was noted. Increased mucosal IL-12, IL-23, IL-1β and IL-6 were indicative of a cytokine milieu that may modulate subsequent T-cell mediated immunity. C. jejuni-driven human monocyte-derived dendritic cell activation was followed by analyses of T cell immune responses utilising flow cytometry and ELISA. Significant increase in Th-17, Th-1 and Th-17/Th-1 double-positive cells and corresponding cytokines was observed. The ability of IFNγ, IL-22 and IL-17 cytokines to exert host defence via modulation of C. jejuni adhesion and invasion to intestinal epithelia was measured by standard gentamicin protection assay. Conclusions Both innate and adaptive T cell-immunity to C. jejuni infection led to the release of IFNγ, IL-22 and IL-17A; suggesting a critical role for this cytokine triad in establishing host anti-microbial immunity during the acute and effectors phase of infection. In addition, to their known anti-microbial functions; IL-17A and IL-17F reduced the number of intracellular C. jejuni in intestinal epithelia, highlighting a novel aspect of how IL-17 family members may contribute to protective immunity against C. jejuni.